ANALYSIS OF KEY ISSUES FOR TRANSPORT DANGEROUS GOODS IN SERBIA - PETROVIĆ, Aleksandra; ARSIĆ, Nebojša; STANOJEVIĆ, Predrag; ŠARKOĆEVIĆ, Živče; PLJAKIĆ, Miloš (Journal of process management and new technologies, 2025)
The transport of dangerous goods poses a significant challenge for the industry, given the potential risks to safety and the environment. This paper analyzes key aspects of regulation and training that affect the efficiency and safety of this sector. Based on a literature review, a survey was developed and conducted in 2023 among 204 respondents, professionals in the field of dangerous goods transport in Serbia. The survey was distributed through electronic channels, allowing for broad access to various industry participants. It encompasses questions that describe six constructs: assessment of the dangerous goods transport environment, legal framework and regulatory familiarity, vehicle classification and documentation, training and certification, vehicle inspection and maintenance, and statistics and procedural aspects. The survey results indicate varying levels of satisfaction with regulation and training. According to the respondents, 35% rated the regulatory process for obtaining a professional competence certificate for dangerous goods advisors as "very good," while 24.8% rated it as "satisfactory." Regarding the training content for certificate renewal, 29.1% of respondents rated the content as "very good," but 10.2% expressed dissatisfaction, suggesting a need for improvement in training programs. The analysis of administrative costs reveals that only 5.8% of respondents rated these costs as "excellent," indicating a need for strategies to reduce costs to enhance accessibility and competitiveness in the dangerous goods transport sector.